Carbon-14 Dating and Stable Isotopes of Carbonates of Late Pleistocene Lacaustrine Sediment in Qa΄a Selma (Jordanian Badia) - Al-Tawash, Balsam (Iraqi Journal of Science, 2025)
A 3.5m borehole was drilled at the northern part of Qa΄a Selma in the northern Jordanian Badia, and is analyzed for radiometric chronology (14C) and stable isotopes (δ18O and δ13 C) at selective depths (50, 85, 150, 310, 350) cm and (30, 50, 85, 130, 150, 190, 230, 270, 310, 350) cm respectively.It provides Late Pleistocene record, with Holocene is missing and not represented.Variations in δ13C and δ18O reveal changes in environmental conditions, induced by climate change. Most of the Late Pleistocene record of the Qa΄a is marked by an arid climatic conditions except for two wet periods (37-32 ka BP) and (15.5-13.9 Ka BP), which are indicating positive precipitation-evaporation balance leading to wetter and/ or cooler climatic conditions.Whereas the arid climatic conditions prevailed the area during the periods ( 32-15.5 ka BP) and (13.9-13.4 Ka BP). The latter dry period may represent one of the short dry episodes that had occurred at the end of the Pleistocene toward the Holocene.